Treatment of associated risk factors in patients with hypertension - Abramczyk, Piotr (Przewodnik Lekarza/Guide for GPs, 2007)
Associated diseases and other factors (not only blood pressure values) significantly increase cardiovascular risk in hypertensives. Obesity, microalbuminuria, hyperuricaemia, obstructive sleep apnoea, hyperglycaemia and hyperlipidaemia are the most important risk factors. Physicians have many strategies (not only pharmacological) to treat most of them. The management of individual patients and choice of antihypertensive therapy should be influenced by associated diseases.